A Tract Reflection on Challenges in Research & Development for New Product Development in the Industrial Sector of Pakistan - Shahzad, Arfan; Al-Swidi, Abdullah Kaid; Golamdin, Abd Ghani (Macrothink Institute, 2013)
New Product Development (NPD) is a strategic issue of successful business in the competitive era of the new global economy. Pakistan is rel atively small, in the Asian region, yet a promising nation in the South East Asian region. Unfortunately, over the past few decades,the country’s export performance has remained sluggish due to slower growth of NPD in her industrial sector.The present st udy conceptually examines the issue of challenges and remedial strategies involved in the context of R&D in the process of NPD in Pakistani industries at-large.Indeed, textile industry is currently a major segment (46%) of the Pakistani industrial sector.In general,the focus of the study is on NPD strategic criteria of the nation.The study discusses global and inward challenges and spells out the steps in formulating a new strategy towards NPD.Pakistan policy makers need to identify and focus on policies towards improvement of FDI inflows, industrial education, technology advancement, R &D budget, and establishing the industrial cluster among several other factors as building blocks of the NDP.